Análisis de la migración del medio impreso tradicional Diario La Prensa, a las plataformas Instagram, Facebook y TikTok - Guaman Llongo, Lizbeth Esthefania (2025)
This research explores the digital transition of Diario La Prensa, a traditional print newspaper, to the social media platforms Instagram, Facebook, and TikTok. The main objective is to examine how the outlet adapted from print to digital formats and to assess the resulting impact on audience engagement, user interaction, and the nature of the content shared. To achieve this, a mixed-methods approach was employed, integrating both qualitative and quantitative research strategies. On the qualitative side, the study involved a literature review and semi-structured interviews. These were conducted using a question guide with two subject experts and the community manager of Diario La Prensa. On the quantitative side, content analysis was carried out using an analytical matrix that evaluated elements such as engagement metrics and content types. The study focused on the official social media platforms managed by the outlet Instagram, Facebook, and TikTok. The sample included five posts per month during the first year of activity on each platform. Given the variability in publication frequency, the sample was selected randomly. The interviews provided insight into the motivations behind the migration to digital media, the metrics used to measure reach and effectiveness, the challenges encountered, and the strategies applied. Results from the content analysis revealed that during the first year, audience interaction across all three platforms remained relatively low. On Instagram and Facebook, images were the most shared content, while TikTok primarily featured video. The most frequently used storytelling approach was crossmedia. Regarding journalistic genres, informative content dominated, with opinion and interpretive pieces appearing only occasionally.